Differentiation of Job Enrichment Implementation Model Toward Employee Engagement and Competitive Advantage Value View from Conventional Perspective and Islamic Perspective At PT Bank Aceh Syariah - Emi Wakhyunia; Asmuni Asmuni; Rizal Agus (International Journal of Artificial Intelligence Research, 2022)
Indonesia is one of the countries that adopt a dual banking system, where conventional banks and Islamic banks operate simultaneously. This causes competition between the two. When compared to conventional banks, the number of Islamic banks in Indonesia is still relatively small, but Islamic banking in Indonesia continues to increase. However, at Bank Aceh Syariah, the increase in the use of Islamic banks is not in line with the increase in the number of employees, where high employee turnover shows their low employee engagement so that it can affect company competition. The goal of this study was to see how disparities in the effect of Job Enrichment on employee engagement and competitive advantage at PT affected employee engagement and competitive advantage. Bank Aceh Syariah is viewed from both a traditional and Islamic standpoint. This study used a quantitative research method with a total sample size of 346 respondents. This study was split into two parts: (1) Model Suitability Testing and (2) Hypothesis Testing with SEM (Structural Equation Model) analysis. The findings of this study show that the effect of job enrichment on employee engagement has a significant impact from both a conventional and Islamic perspective, as well as the effect of job enrichment on competitive advantage from both a conventional and Islamic perspective, which has a significant impact, and the effect of employee engagement. From both a conventional and an Islamic standpoint, competitive advantage has a tremendous impact. When the results of the influence of each variable seen in the Islamic perspective are compared to the influence of the variables seen in the conventional perspective, the results of the influence of each variable seen in the Islamic perspective have a higher value. This demonstrates that each of the employees of PT. Bank Aceh Syariah has a person who believes in and fears Allah SWT, and that Islamic values and sharia principles are observed in their work.